The Trap of Toxic Relationships in Dating: The Case of Five Female Students in Palu City - Sofya Lestari; Zaiful Zaiful; Moh. Nutfa Moh. Nutfa (Eduvest - Journal of Universal Studies, 2024)
Toxic Relationship becomes a trap in teenage dating relationships so that one party feels depressed and disadvantaged, even threatening life safety, especially for women. This study aims to explain the forms and motives for maintaining toxic relationships in dating relationships. A descriptive qualitative approach was used to explore the stories (cases) of five female students who were victims of toxic relationships in Palu City, Central Sulawesi. Data were obtained from in-depth interviews and brainstorming and reinforced from literature studies and news sources. Data were analyzed interpretatively. Data reliability was obtained from data triangulation. The results showed that the forms of toxic relationships in dating are physical violence, sexual harassment, verbal violence, intimidation, and possessiveness. The reasons why teenage girls maintain toxic relationships are because: (1) hope that the partner can change bad behavior to good; (2) the family has known each other; and (3) still have trust in the partner even though they have experienced physical violence, sexual violence and poor mental health. Getting out of a toxic relationship is not easy because the factors of hope for love, family, and trust are still the motives for maintaining a dating relationship.